Effect of the segmented fin height on the air-side performance of serrated welded spiral fin-and-tube heat exchangers - Keawkamrop, Thawatchai; Mesgarpour, Mehrdad; Dalkılıç, Ahmet Selim; Ho Seon Ahn; Mahian, Omid (Case studies in thermal engineering)
Serrated welded spiral fin-and-tube heat exchangers (SWSFTHXs) are experimentally investigated. The work primarily focuses on the effects of the segmented fin height (h(s)) with various fin pitches (f(p)) on the air-side performance (ASP). Experimental results show that SWSFTHXs provide a higher air-side heat transfer coefficient than the plain welded spiral fin-and-tube heat exchangers (PWSFTHXs) at the same f(p). The h(s) has a significant effect on the Nusselt number (Nu) and Colburn factor (j), whereas f(p) clearly has a greater effect on the friction factor (f) and Euler number (Eu) than h(s). Furthermore, the Nu, j, f, and Eu correlations for PWSFTHXs and SWSFTHXs are also proposed.